Hematologic Tumor Cell Resistance to the BCL-2 Inhibitor Venetoclax: A Product of Its Microenvironment? - Leverson, Joel D.; Cojocari, Dan (Frontiers in Oncology, 2018)
BCL-2 family proteins regulate the intrinsic pathway of programmed cell death (apoptosis) and play a key role in the development and health of multicellular organisms. The dynamics of these proteins’ expression and interactions determine the survival of all cells in an organism, whether the healthy cells of a fully competent immune system or the diseased cells of an individual with cancer. Anti-apoptotic proteins like BCL-2, BCL-XL and MCL-1 are well known for maintaining tumor cell survival and are therefore attractive drug targets. The BCL-2-selective inhibitor venetoclax has been approved for use in chronic lymphocytic leukemia and is now being studied in a number of other hematologic malignancies. As clinical data mature, hypotheses have begun to emerge regarding potential mechanisms of venetoclax resistance. Here, we review accumulating evidence that lymphoid microenvironments play a key role in determining hematologic tumor cell sensitivity to venetoclax.